(untitled) (Nigerian Journal of Technology, 2020)
Synoptic findings by researchers have revealed tremendous physic-chemical improvements of polymer modified mixes over the conventional asphalt. Traditionally, laboratory mechanical properties were carried out for asphalt testing, but cannot calibrate simple performance test (SPTs) criteria for fatigue and field performance. Marshall test-sized specimens of polymer asphalt mixtures were engineered with arbitrary contents of 0 to 3.0% polypropylene waste admixed with 4.5 to 6.5% bitumen contents based on relevant literature. Creep deformation involves uniaxial static creep (USC) test using BS 598-111. Morphological examinations were test with Hitachi S-4700 field-emission scan-electron-microscope (FE-SEM). Thirdly, thermal degradation was determined using Shimadzu TGA-50 thermo-gravimetric analyzer. The results showed creep resistivity with fatigue recovery of 23.2% and 28.9% strain reduction at 10oC and 60oC respectively from the optimal 2.0% polypropylene and 6.0% bitumen compared to the control mix. Also, the same mix produced well dispersed and better enhanced pore packaging micro-structure capable of resisting ageing volatization under severe traffic and environmental loading conditions considered. http://dx.doi.org/10.4314/njt.v39i3.3